2006
DOI: 10.1590/s1517-45222006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da descentralização nas relações intergovernamentais: o Brasil em perspectiva comparada

Abstract: Este artigo analisa os efeitos de políticas de descentralização na evolução das relações de poder entre presidentes, governadores e prefeitos no Brasil, após o fim do estado desenvolvimentista. Compara as conseqüências da descentralização pós-desenvolvimentista no Brasil com aquelas resultantes de processos similares na Argentina, na Colômbia e no México. Para explicar as diferenças observadas entre os países, o artigo desenvolve uma teoria seqüencial da descentralização, a qual é aplicada ao caso brasileiro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
29

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 8 publications
0
5
0
29
Order By: Relevance
“…However, the implementation of national policies increasingly depends on the national government's capacity of coordinating the instruments that are available to stimulate subnational governments to follow policy guidelines (ARRETCHE, 2012;BICHIR, 2011). Departing from the works of Rodden (2005) and Falleti (2006), Arretche (2012) makes a significant contribution by showing that it is not possible to conceive the decentralization of policy-making as equivalent to policy decision-making autonomy. Arretche (2012) found that, contrary to 'conventional wisdom', the Brazilian federation is quite centralized, since the national level has several institutional mechanisms that reinforce its authority vis-à-vis the states and the municipalities, like exclusive legislative authority regarding numerous issues, regulatory power, capacity to control the public spending of subnational governments, etc.…”
Section: Implementing Social Policy In Federal Contexts: Multi-level mentioning
confidence: 99%
“…However, the implementation of national policies increasingly depends on the national government's capacity of coordinating the instruments that are available to stimulate subnational governments to follow policy guidelines (ARRETCHE, 2012;BICHIR, 2011). Departing from the works of Rodden (2005) and Falleti (2006), Arretche (2012) makes a significant contribution by showing that it is not possible to conceive the decentralization of policy-making as equivalent to policy decision-making autonomy. Arretche (2012) found that, contrary to 'conventional wisdom', the Brazilian federation is quite centralized, since the national level has several institutional mechanisms that reinforce its authority vis-à-vis the states and the municipalities, like exclusive legislative authority regarding numerous issues, regulatory power, capacity to control the public spending of subnational governments, etc.…”
Section: Implementing Social Policy In Federal Contexts: Multi-level mentioning
confidence: 99%
“…A literatura tem analisado a descentralização no contexto federativo e de relações intergovernamentais (Melo 1996;Kugelmas & Sola 1999;Arretche 1999;Abrucio 2005;Almeida s.d. 2005;Falleti 2006), mas não como política de gestão das cidades. O estudo do tema pode ser ampliado, de forma comparada, pois ao menos as seguintes metrópoles brasileiras têm adotado a descentralização/desconcentração territorial (Tabela 1).…”
unclassified
“…Segundo Falleti (2006), "A descentralização é um processo de reforma do Estado composta por um conjunto de políticas públicas que transfere responsabilidades, recursos ou autoridades de níveis mais elevados do governo para níveis inferiores, no contexto de um tipo específico de Estado." (p. 33) O processo de descentralização se inicia com a transição de um tipo de Estado "desenvolvimentista" para um Estado do tipo "bem público".…”
Section: Descentralização E Regionalizaçãounclassified
“…A descentralização administrativa do financiamento dos serviços de saúde pública ocorreu na década de 1990 (Falleti, 2006).…”
Section: Descentralização E Regionalizaçãounclassified